2000
DOI: 10.1161/01.cir.102.22.2677
|View full text |Cite
|
Sign up to set email alerts
|

Fish Oil–Derived Fatty Acids, Docosahexaenoic Acid and Docosapentaenoic Acid, and the Risk of Acute Coronary Events

Abstract: Background-Previous findings concerning the serum levels of fish-derived (n-3) fatty acids and coronary heart disease are inconsistent. The purpose of this study was to investigate the association between the serum n-3 end-product fatty acids docosahexaenoic acid (DHA), docosapentaenoic acid (DPA), and eicosapentaenoic acid and the risk of acute coronary events in middle-aged men. Methods and Results-We studied this association in the Kuopio Ischaemic Heart Disease Risk Factor Study, a prospective population s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
192
1
7

Year Published

2001
2001
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 278 publications
(203 citation statements)
references
References 19 publications
3
192
1
7
Order By: Relevance
“…The average DHA 1 EPA intake in our study (0?1 g/d) was much lower in comparison to that of other studies. Our results agree with other studies which have shown that fish intake or markers of fish intake (plasma PUFA) do not significantly impact LDL-C or TC levels (17,23) . The 24 h calculated DHA 1 EPA intake in our study was also less than the American Heart Association (AHA) recommendation (at least 0?5-1?0 g of n-3 fatty acids daily to achieve cardioprotective effects), which may explain the lack of association in the models where HDL-C, LDL-C and TC were the independent variables (24) .…”
Section: Discussionsupporting
confidence: 93%
“…The average DHA 1 EPA intake in our study (0?1 g/d) was much lower in comparison to that of other studies. Our results agree with other studies which have shown that fish intake or markers of fish intake (plasma PUFA) do not significantly impact LDL-C or TC levels (17,23) . The 24 h calculated DHA 1 EPA intake in our study was also less than the American Heart Association (AHA) recommendation (at least 0?5-1?0 g of n-3 fatty acids daily to achieve cardioprotective effects), which may explain the lack of association in the models where HDL-C, LDL-C and TC were the independent variables (24) .…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the Kuopio Ischaemic Heart Disease Risk Factor Study showed that the men with the highest quintile of serum DHA plus DPA (>3.58% of total fatty acids) had a 44% reduced risk of acute coronary events compared with men in the lowest quintile (<2.38% of total fatty acids), and there were no associations with EPA levels (6). The significance was due to DHA plus DPA, not just DHA alone.…”
Section: Introductionmentioning
confidence: 98%
“…A growing body of literature supports a protective role of fish intake and of essential dietary long-chain polyunsaturated fatty acids in cardiovascular disease (Dolecek & Granditis, 1991;Ascherio et al, 1995;Daviglus et al, 1997;Hopper et al, 1999;Oomen et al, 2000;Rissanen et al, 2000;Hallgren et al, 2001;Iso et al, 2001;Yuan et al, 2001) including a reduction of the risk of sudden cardiac death (Siscovick et al, 1995;Albert et al, 1998). There are several potential mechanisms for this protection including antithrombotic (Kristensen et al, 1989;Prisco et al, 1995) and anti-arrhythmic effects (Marchioli et al, 2002), decreased heart rate variability (Christensen et al, 1997) and resting blood pressure (Knapp, 1989), decreased serum LDL cholesterol and triglyceride concentrations (Agren et al, 1996) and increased insulin sensitivity (Torjesen et al, 1997;Mori et al, 1999).…”
Section: Introductionmentioning
confidence: 99%